Routledge handbook of masculinities, conflict and peacebuilding - Myrttinen, Henri (Routledge handbooks., 2025)
"This handbook broadens and engages with current debates on men and masculinities in conflict and peacebuilding. Through an expansive range of chapters across a unique array of geographical settings, the volume shatters prevailing assumptions about men's relationship to conflict and its wake. Situated across scholarship, policy, and practice, the contributions offer new possibilities for a more complex and complete picture of the gendered tapestries of conflict, peace, and the spaces in between. The handbook combines feminist, intersectional, relational, decolonial, and queer perspectives on the conceptualisation of masculinities in conflict and peacebuilding. This approach provides us with the tools to go beyond direct, physical, conflict-related violence to examine less visible forms of violence and power, as well as other ways in which masculinities interact with conflict and peace. In doing so, the book permits a multi-faceted view of men's roles, relationships, vulnerabilities, and non-violent agencies in conflict and peacebuilding across scholarship, policy, and practice. This book will be of much interest to students of gender, masculinities, peace and conflict studies and International Relations"--